Microsatellite Markers for Cariniana legalis (Lecythidaceae) and Their Transferability to C. estrellensis - Evandro Vagner Tambarussi; Alexandre Magno Sebbenn; Maria Andréia Moreno; Elza Martins Ferraz; Paulo Yoshio Kageyama; Roland Vencovsky (Applications in Plant Sciences, 2013)
Premise of the study: Microsatellite primers were developed in the neotropical tree species Cariniana legalis (Lecythidaceae) to investigate its genetic diversity, mating system, and gene flow.